Analisis Pengaruh Kepemimpinan terhadap Pengembangan Karir dan Dampaknya pada Kinerja Karyawan. - Yanti, Lutfa Febi; Sinollah (Fakultas Ekonomi dan Bisnis, Universitas Islam Raden Rahmat Malang, 2023)
The purpose of this study was to identify and analyze the influence of leadership and career development on employee performance, both directly and indirectly. The design of this study uses a quantitative approach with data collection methods using a questionnaire on employees of PT Pindad Enjiniring Indonesia with a sample of 56 employees. The analytical method in this study uses path analysis (Path Analisys). The results in this study indicate the influence of: (1) leadership has a significant direct effect on career development. (2) leadership is not directly significant to employee performance. (3) career development directly has a significant effect on employee performance. (4) Leadership indirectly has no significant effect on employee performance through career development. For this reason, if a leader wants to improve employee performance by paying attention to employee career development.